Species of Lamiinae (Insecta, Coleoptera, Cerambycidae) from east Paraná State (Brazil), with new geographic records - de Barros, Rafael C.; Da Fonseca, Mailson G.; Vendramini, Vinicius E.; de Arvarenga Julio, Carlos E. (Zootaxa, 2019)
A list of species of Lamiinae (Cerambycidae) collected in Iguaçu National Park (PNI) during the period from March 2012 to December 2015, using different collection methods, is provided. A total of 134 species were sampled, all recorded for the first time in the PNI and including 38 new distribution records for the state of Paraná, and one new record for Brazil. The geographic distribution and material examined are stated for each species. Each new record also accompanied by an illustration of the species.